2011
DOI: 10.1039/c1ce05294b
|View full text |Cite
|
Sign up to set email alerts
|

Control of polymorphic transition inducing preferential enrichment

Abstract: Preferential enrichment is an unusual symmetry-breaking enantiomeric resolution phenomenon that is initiated by the solvent-assisted solid-to-solid transformation of a metastable polymorphic form into a thermodynamically stable one during crystallization from the supersaturated solution of a certain kind of racemic crystals. On the basis of the proposed mechanism of preferential enrichment, both induction and inhibition of preferential enrichment were successfully achieved by controlling the mode of the polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 56 publications
1
37
3
Order By: Relevance
“…Meanwhile, semi‐oxalate molecules directly connect with each other by O‐H···O hydrogen bond (O3···O6: 2.63Å) forming a 1D chain structure along the a ‐axis [graph set: C 1 1 (5)] to contribute to the formation of DL ‐sheet pair structure. This crystal structure is quite different from those of racemic crystals that thus far showed PE; the latter consisted of heterochiral cyclic DL dimer chains as well as homochiral 1D d chains and L chains to form a heterochiral 2D sheet structure …”
Section: Resultscontrasting
confidence: 66%
See 4 more Smart Citations
“…Meanwhile, semi‐oxalate molecules directly connect with each other by O‐H···O hydrogen bond (O3···O6: 2.63Å) forming a 1D chain structure along the a ‐axis [graph set: C 1 1 (5)] to contribute to the formation of DL ‐sheet pair structure. This crystal structure is quite different from those of racemic crystals that thus far showed PE; the latter consisted of heterochiral cyclic DL dimer chains as well as homochiral 1D d chains and L chains to form a heterochiral 2D sheet structure …”
Section: Resultscontrasting
confidence: 66%
“…Preferential enrichment (PE) is a unique enantiomeric resolution phenomenon that is caused by the polymorphic transition of an incipient metastable polymorphic form into a thermodynamically more stable form during crystallization from the supersaturated solution of a certain kind of racemic crystals (Fig. ) . We have proposed a mechanism for the occurrence of PE, based on extensive studies of the first‐generation chiral organic compounds of onium sulfonate salts that showed excellent PE (Fig.…”
mentioning
confidence: 99%
See 3 more Smart Citations